Tectonic environments of South American porphyry copper magmatism through time revealed by spatiotemporal data mining. Issue 12 (9th December 2016) - Butterworth, N.; Steinberg, D.; Müller, R. D.; Williams, S.; Merdith, A. S.; Hardy, S.
Abstract: Porphyry ore deposits are known to be associated with arc magmatism on the overriding plate at subduction zones. While general mechanisms for driving magmatism are well established, specific subduction‐related parameters linking episodes of ore deposit formation to specific tectonic environments have only been qualitatively inferred and have not been formally tested. We develop a four‐dimensional approach to reconstruct age‐dated ore deposits, with the aim of isolating the tectonomagmatic parameters leading to the formation of copper deposits during subduction. We use a plate tectonic model with continuously closing plate boundaries, combined with reconstructions of the spatiotemporal distribution of the ocean floor, including subducted portions of the Nazca/Farallon plates. The models compute convergence rates and directions, as well as the age of the downgoing plate through time. To identify and quantify tectonic parameters that are robust predictors of Andean porphyry copper magmatism and ore deposit formation, we test two alternative supervised machine learning methods; the "random forest" (RF) ensemble and "support vector machines" (SVM). We find that a combination of rapid convergence rates ( 100 km/Myr), subduction obliquity of 15°, a subducting plate age between 25–70 Myr old, and a location far from the subducting trench boundary (>2000 km) represents favorable conditions for porphyry magmatism and related ore deposits to occur. These parameters are linked to the availability of oceanic sediments, the changing small‐scale convection around the subduction zone, and the availability of the partial melt in the mantle wedge. When coupled, these parameters could influence the genesis and exhumation of porphyry copper deposits. Key Points: Time‐dependent plate reconstruction kinematics applied to South American porphyry copper deposit data Machine learning classification used to identify mechanisms for porphyry copper magmatism Subducting slab age, convergence rates and directions, and trench extent control porphyry genesis